Validation of Spleen Stiffness Measurement for Screening of High-risk Esophageal Varices Among Cirrhotic Patients in Indonesia: A Single-Center Cross-sectional Study - Saut Horas Hatoguan Nababan; Gita Aprilicia; Pitt Akbar; Kemal Fariz Kalista; Chyntia Olivia Maurine Jasirwan; Juferdy Kurniawan; Cosmas Rinaldi A. Lesmana; Andri Sanityoso Sulaiman; Irsan Hasan; Rino Alvani Gani (Acta Medica Indonesiana)
Background: Spleen stiffness measurement (SSM) is a recently developed non-invasive method for predicting clinically significant portal hypertension and esophageal varices in compensated advanced liver disease or cirrhosis. This study aims to validate the accuracy of SSM for screening high-risk esophageal varices among cirrhotic patients in Indonesia. Methods: This is a single-center, cross-sectional study. Patients with liver cirrhosis who underwent endoscopy at Cipto Mangunkusumo Hospital, Jakarta were included. Clinical data and data from laboratory tests, endoscopy, liver, and spleen stiffness measurement by transient elastography (TE) were collected. A 100 Hz spleen-dedicated TE probe was used for SSM. Results: Of 86 patients, 52 had high-risk esophageal varices. The median (IQR) value of SSM were significantly higher in patients with high-risk varices [36.1 kPa (IQR 21.5-59.1) vs. 70.3 kPa (IQR (52.2-86.0); p<0.001). SSM with a low cutoff value of 20 kPa had sensitivity and negative predictive value of 98.1% and 87.5%, respectively. The high cutoff value of 70 kPa had specificity and positive predictive value of 82.4% and 81.3%, respectively. Conclusion: SSM is useful for screening high-risk esophageal varices. Furthermore, the new dual cutoff value can help rule-in and rule-out high-risk esophageal varices among cirrhotic patients in Indonesia.